Pathologic anatomy of the fetus from mothers with complicated pregnancy - Yakovtsova, A.F.; Markovskiy, V.D.; Sorokina, I.V.; Gubina-Vakulik, G.I.; Gargin, V.V.; Omelchenko, O.A.; Myroshnichenko, M.S.; Galata, D.I.; Potapov, S.N.; Shapkin, A.S. (Pathologia, 2013)
The article describes the morphological changes in the heart, testes, bone marrow, thymus, spleen of fetuses from mothers with complicated pregnancy. It is noted that the study of morphological features of major systems of the fetus in various pathological conditions of the mother allows to predict the presence and nature of the lesions of these systems in postnatal ontogenesis.